Looking At The Future Of Indonesia In GEDSI Mainstreaming Through The Prabowo-Gibran Vision And Mission Document - Fahmi Idris Sudrajat (Eduvest - Journal of Universal Studies, 2024)
Gender equality, disability and social inclusion (GEDSI) is a concept which enables the realization of sustainable inclusive development. The mainstreaming of GEDSI is also explicitly or implicitly contained in the vision and mission documents of the presidential and vice-presidential candidates Prabowo-Gibran, who are the winning pair of the election based on quick counts. In contrast to previous studies that tend to analyze policy documents that have been issued by agencies or institutions, this study aims to dissect the Prabowo-Gibran pair's ideas in implementing the GEDSI concept contained in the vision and mission document. The analysis of term frequency and density using the R application was carried out to calculate the frequency and density of keywords, while content analysis was used to understand the context of each word occurrence. This research is expected to make it easier to see Indonesia's future in mainstreaming GEDSI. The results found that 33 times the keywords appeared in the Prabowo-Gibran mission vision document, the context of the appearance of keywords contained in the Prabowo-Gibran mission vision document at least has a serious commitment to mainstreaming GEDSI.